Android How To Program - Dietel,Paul; Dietel,Abbey; Dietel,Harvey (Boston Pearson Education Limited, 2015)
This book presents leading-edge mobile computing technologies for students,instructors and professional software developers.With this book you'll learn about the dynamic world of Android smartphone and tablet app development with the Android software Development kit(SDK),the Java programming language,the Android Development Tools IDE, and the new and rapidly evolving Android studio
Includes Index p. 709:728
3
Keywords: Android(Electronic resourse -- Programming; Programming Techniques